Interface-dependent activity and selectivity for CO2 hydrogenation on Ni/CeO2 and Ni/Ce0.9Sn0.1Ox. (15th May 2022) - Zhang, Zhiqiang; Tong, Yunyan; Fang, Xiuzhong; Xu, Junwei; Xu, Xianglan; Wang, Xiang
Graphical abstract: Highlights: Interface microstructure of Ni/CeO2 greatly affects selectivity & activity for CO2 hydrogenation. The activity for CO2 hydrogenation follows Ni/CeO2  > Ni/0.1SnO2 -0.9CeO2  > Ni/Ce0.9 Sn0.1 Ox . Ni/CeO2 and Ni/0.1SnO2 -0.9CeO2 show CH4 selectivity, while Ni/Ce0.9 Sn0.1 Ox CO selectivity. Sn 4+ of Ni/Ce0.9 Sn0.1 Ox immigrating to Ni causes Sn 4+ enrichment and Ni-O-Sn-O-Ce interface. Sn 4+ in interface inhibits formate path for CH4 while favors CO yield. Abstract: To study the importance of interface microstructure on reactivity for CO2 hydrogenation, Ni/CeO2, Ni/Ce0.9 Sn0.1 Ox and Ni/0.1SnO2 -0.9CeO2 catalysts were prepared, whose support is pristine CeO2, Sn-doped CeO2 -based solid solution, and the mixture of SnO2 and CeO2 in sequence with a Sn/Ce molar ratio of 1:9 in the latter two supports. The intrinsic activity of the catalysts for CO2 hydrogenation followed the order: Ni/CeO2  > Ni/0.1SnO2 -0.9CeO2  > Ni/Ce0.9 Sn0.1 Ox . Ni/CeO2 and Ni/0.1SnO2 -0.9CeO2 showed CH4 selectivity, while Ni/Ce0.9 Sn0.1 Ox CO selectivity. The strong interaction between Sn cations and Ni species in Ni/Ce0.9 Sn0.1 Ox resulted in the immigration of Sn cations to Ni species to form the Ni-O-Sn-O-Ce interface, distinctly differing from the Ni-O-Ce interface in Ni/CeO2 and the Ni-O-Ce plus Ni-O-Sn interfaces in Ni/0.1SnO2 -0.9CeO2 . The enrichment of Sn cations as acidic sites on the Ni/Ce0.9 Sn0.1 Ox surface decreased evidently the chemisorption of CO2 and inhibited the generation of HCO3 *, thus inhibiting the formate path for CH4 . Conversely, the presence of Sn cations in the interface favored the generation of carbonates, thus promoting CO yield. This work shows the activity and selectivity for CO2 hydrogenation are highly dependent on microstructure of an interface in oxide-supported Ni catalysts.